MODEL PENDUGAAN KONSUMSI KAYU LAPIS OLEH RUMAH TANGGA DI DAERAH JAWA TENGAH DAN JAWA TIMUR - Rachman Effendi; Buhannan Buhannan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The development of domestic market of plywood relies heavily on the effective demand for plywood or buying power in real sense. This research is aimed at studying the pattern of relation ship between the consumption of plywod by household in Central Java and East Java and some factors influencing it.The average volume of plywood annually consumed by household is of 0.0152 m3 per year per family (with average of 3. 6 persons/family). The variables that influence the effective demand of plywood are family income, price of plywood and the number of family member. The elasticity of the demand of the three factors is of 0.3365 implying that the consumption of plywood is inelastic to the change of the three factors.